Intravenous N-acetylcysteine in severe cutaneous drug reaction treatment: A case series - Hasan, Md Jahidul (SAGE Open Med Case Rep, 2020)
Drug-induced serious adverse reaction is an unpleasant event with high rate of mortality. Stevens–Johnson Syndrome and toxic epidermal necrolysis are most common among the serious adverse drug reactions. There is no selective drug therapy for the management of serious adverse drug reactions-associated mucocutaneous blisters. The use of N-acetylcysteine in the treatment of mucocutaneous blisters has limited evidence worldwide. Three cases of toxic epidermal necrolysis or Stevens–Johnson Syndrome-associated mucocutaneous blisters are presented in this study where intravenous N-acetylcysteine (600 mg, every 8 h) was given in early hospitalization hours for the treatment of mucocutaneous fluid-filled blisters. Here, one patient with toxic epidermal necrolysis received intravenous immunoglobulin along with intravenous N-acetylcysteine and the other two patients (toxic epidermal necrolysis/Stevens–Johnson Syndrome) received only N-acetylcysteine intravenously. In response, mucocutaneous fluid-filled blisters stopped progressing within 48 h and were healed within 2 weeks of admission in the intensive care unit. Thus, intravenous N-acetylcysteine with or without having intravenous immunoglobulin in the treatment of serious adverse drug reactions-associated mucocutaneous blisters may be an effective therapeutic option for better clinical outcome.